Tax Education for MSMEs: Solutions for Compliance and Business Optimization - Astini, Yuli; Setiawati, Elvina (Edumedia Solution, 2025)
This community service project aims to enhance tax literacy and compliance among Micro, Small, and Medium Enterprises (MSMEs) in Mataram, West Nusa Tenggara, through practical education on Income Tax Return (SPT) filing. Implemented in two stages—a public tax consultation booth and a targeted interactive workshop—the program applied simulation-based learning using Forms F-1770 and F-1771, adjusted to participants’ business contexts. Evaluation using pre-test and post-test instruments revealed an average 30.6% increase in technical understanding, demonstrating the effectiveness of practice-based, participatory methods. The project also identified digital adaptation and regulatory complexity as key challenges, reinforcing the need for contextual and ongoing tax education efforts. The short-term gains in comprehension and reporting confidence indicate strong potential for long-term improvements in tax compliance and administrative sustainability among MSMEs. This initiative supports Indonesia’s broader fiscal transformation efforts, especially in light of the declining national tax ratio index